Hukum Islam sebagai Hukum Progresif - A. Malthuf Siroj (Universitas Nurul Jadid, 2021)
Progressive law (hukum progresif) as a discourse emerged as a response to law enforcement in Indonesia which was concerning, because there had been commercialization and legal engineering by a group known as the judicial mafia so that it deviated from Indonesia's ideals as a state of law. It was Prof. Satjipto Rahardjo who initiated progressive law. Conceptually, progressive law wants to restore the function of law so that it is in accordance with its objectives, namely upholding justice and realizing the benefit of humans. Thus, law according to the concept of progressive law must be dedicated to humans, not the other way around, and to realize justice, the law must always develop dynamically, it must not stagnate in the form of a rigid statutory text. This study wants to see whether Islamic law can also be called progressive law. From the results of the study, it was found that conceptually Islamic law can be categorized as progressive law, although not completely, because Islamic law originates from God's divine revelation